Pemanfaatan KBBI Daring dalam Pembelajaran Bahasa Indonesia di Sekolah Indonesia Kota Kinabalu, Malaysia. - Nur Afiqa Apriandini; Ramly; Nurhusna (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to describe the level of accessibility, integration, and utilization of the Digital Kamus Besar Bahasa Indonesia (KBBI) in Indonesian language learning at Sekolah Indonesia Kota Kinabalu Senior High School, Malaysia. This research employed a descriptive qualitative approach. The informants consisted of 15 participants, including students and Indonesian language teachers. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data display, and conclusion drawing. The results show that students’ accessibility to the Digital KBBI is still limited, influenced by factors such as device availability, internet connectivity, and school policies regarding gadget use. The integration of the Digital KBBI in learning has been implemented through teacher guidance and school literacy programs; however, it has not been fully optimized. The utilization of the Digital KBBI helps students understand vocabulary and improve their Indonesian language skills, although it still requires guidance and adequate supporting facilities. In conclusion, the Digital KBBI has significant potential to support Indonesian language learning, but its utilization remains suboptimal due to limited access and integration. Therefore, this study recommends enhancing digital literacy, providing supporting facilities, and conducting training on the use of the Digital KBBI for both students and teachers